Franz Kafka: The metaphor of the "burrow" as shelter and dug - Costanzo, Giovanna (Itinerari, 2024)
The parable of the Kafkaesque script allows us to realize that it becomes more enigmatic more it becomes the figure of the loneliness of the Western Jew without memory and without roots, especially after 1917, the year in which he learns that he has fallen ill with tuberculosis, feeling as condemnation the anguish of Kierkegaardian aesthetic life. In this period, we can see the intellectual fatigue towards a time perceived as resigned and without find redemption, the inexhaustible search for the truth through writing. The Burrow represents the emblem and the epilogue of this parable.